(untitled) (Ibrahim Cardiac Medical Journal, 2021)
Background & Objective: The purpose of the study was to evaluate the clinical presentation and severity of community acquired pneumonia in adults. Methods: The present cross-sectional study was conducted in Sir Salimullah Medical College & Mitford Hospital, Dhaka over a period of 1 year. Patients admitted with the symptoms and signs suspected of pneumonia and confirmed by clinical examination and necessary investigations were the study population. The baseline characteristics, patients’ behavioural factors, presenting complaints, co-morbidities, examination findings and investigations were recorded. Data were processed and analyzed using software SPSS (Statistical Package for Social Sciences), version 11.5. The test statistics used to analyze the data were descriptive statistics. Result: In the present study, a large proportion of patients were 50 years or more than 50 years with mean age of the patients being 46.4 ± 13.3 years. A male predominance (58%) was observed in the series. Over half (56%) of the patients was smoker and 8% were alcoholic. Fever (90%) and purulent sputum (70%) were the common complaints. The second most common complaints were chest pain and haemoptysis (each of 44%). Thirty eight percent of the patients had dyspnoea and a very few had other symptoms. Eighteen percent of the patients had COPD, another 18% had diabetes and 4% had cardiac insufficiency. About one-quarter (24%) of the patients had agitation stupor, 88% bronchial breathing and 68% crackles. Right lower lobe (31%) and right middle lobe (26%) were commonly affected by pneumonia of the patients detected with a chest X-ray. Assessment of severity pneumonia by CURB-65 score shows that 83% of the patients had mild (score 0 – 1) CAP, 12% had moderate (score 2) and 5% had severe CAP (score 3 or more).Over two-thirds (68.5%) of the patients exhibited positive sputum for Gram’s stain. Conclusion: The study concluded that CAP is more likely to occur in older males with preexisting comorbidities like diabetes and COPD. Fever and purulent cough are the predominant presentation of CAP followed by chest pain and haemoptysis. Pneumonic consolidation on chest X-ray and +ve gram stain are diagnostic of CAP, while raised total count of WBC with neutrophilic leucocytosis are supportive to it. Assessing pneumonia severity by CURB-65 scoring system revealed that severe pneumonia (score 3 or more) is now a rarity. Patient evaluation should focus on severity of illness, patient age, comorbidities, clinical presentation, epidemiologic setting, and previous exposure. The majority of patients with CAP are treated empirically based on the most common pathogen(s) associated with the condition. Ibrahim Card Med J 2020; 10 (1&2): 51-56